Development of CFD porous model parameters of Korean PWR spent nuclear fuel assemblies for thermal analysis - Do Yun Kim; Han-Seop Song; Jae-Ho Jeong; Seung-Hwan Yu (Nuclear Engineering and Technology)
This study focused on developing and validating porous model parameters to accurately estimate the thermal behavior of spent nuclear fuel assemblies for computational fluid dynamics simulations. These assemblies are stored in Korean pressurized water reactors (PWRs) under dry storage conditions. Korean PWR fuel assemblies were categorized into four distinct types based on their configuration, facilitating the calculation of effective thermal conductivities and flow resistance coefficients. These parameters are crucial for simulating heat transfer and determining the peak cladding temperature (PCT), ensuring the thermal safety of stored nuclear fuel. The validation of the proposed porous model against explicit two-dimensional and three-dimensional simulations demonstrated its efficacy and reliability in enhancing the thermal analysis of spent fuel assemblies, highlighting the significance of accurately calculating the porous model parameters in the safety assessment of nuclear fuel storage. Furthermore, the study assessed the sensitivity of variables influencing temperature during spent nuclear fuel storage, focusing on flow resistance coefficients, control rod effect, and basket size. The findings revealed that variations in flow resistance and the presence of control rods minimally impacted PCT, whereas basket size significantly influenced temperature, underscoring its importance in the thermal analysis of nuclear fuel storage systems.